Building a financial inclusion index and analyzing its impact on unemployment - Sari, Yollit Permata; Yeni, Isra; Pebriyani, Dewi; Akbar, Urmatul Uska; Putra, Hari Setia; Artha, Dwi Rani Puspa (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
Financial inclusion has garnered attention from policymakers globally due to its potential to spur economic growth, alleviate poverty, and decrease unemployment. This study focuses on estimating the financial inclusion index across ten Southeast Asian countries utilizing principal component analysis. The objective is to identify the most representative index capable of accurately reflecting the financial inclusion indicators specific to each country. Additionally, the research seeks to explore the impact of financial inclusion on the unemployment rate. Data spanning from 2011 to 2021 were sourced from the World Bank. By employing panel regression estimation, the study reveals that digital financial inclusion does not significantly influence the unemployment rate, as indicated by a significance value of 0.118. Furthermore, a similar lack of impact was observed concerning GDP. Conversely, the inflation rate and education level variables affected the unemployment rate significantly, with significance values of 0.028 and 0.021, respectively. These empirical results suggest that policymakers should implement strategies to enhance financial inclusion, such as reducing the costs associated with financial services, offering incentives to the informal sector, and promoting education on the significance of financial instruments and institutions.